Different analytical methods for estimating the heavy metals in fish products available in the Iraqi local markets by atomic absorption technique - Hamad F. Musa Al – Jubouri; Sarhan A Salman (Tikrit Journal of Pure Science, 2019)
The present study aims to estimate heavy metals (Cadmium, Lead, Copper, Zinc and Iron) by different analytical methods in local and imported fish products such as the following samples: (White tuna meat small pieces) Thailand produce, (Sardines with vegetable oil pepper, slices without heads) produced by Morocco, (Fish fillet without bones) Vietnam production (live Carp fish from ponds and live Carp fish from the Tigris River) Iraq production, and (Tuna cut small) Turkey production, The concentrations of above-mentioned elements in the target samples were determined by the flame atomic absorption device . Concentrations of heavy metals were estimated at (ppm) as follows : Cadmium values (0.48 - 2.05 ppm) , While Lead values (0.66- 2.90 ppm), The values of Zinc (2.99 - 19.14 ppm) , Copper values (0.15 - 2.66 ppm) , The values of Iron (15.47-3.28 ppm), The results showed that the best method of extraction was the method of digestion which showed better results than the other two methods (ultrasound method and Ashing method). The results showed that the levels of Cadmium and Copper in some products are higher than the limits allowed by the World Health Organization (WHO) and World Food Organization (FAO) while the values ​​of Lead, Iron and Zinc were within the limits allowed .